On Some Issues of Foreign Language Course Modeling and Theory Designing - Hayryan, Karen (Armenian Folia Anglistika, 2009)
Foreign Language teaching is a bilateral process of transferring and receiving/understanding knowledge which can be studied from different points of view. The successful realization of a foreign language course is predominantly conditioned by the relevance of highly productive texts.The article discusses the problems of text designing, analysis, evaluation, as well as those connected with revealing its intrinsic instructive opportunities in the framework of text linguistics (grammar) and text theory.Several problems connected with text modeling i.e. text building and elaboration of its effective versions are discussed from the perspective of text theory. This theory is supposed to serve as a stable ground for teaching versatile skills and abilities of foreign language communication.